TALENT MANAGEMENT PRACTICES AND GENDER IMBALANCE IN INSTITUTIONS: IMPACT ON INSTITUTIONAL PERFORMANCE - Abdulkarim S. Praise; Jainaba M.L. Kah; Lukman Raimi (Dinasti Publisher, 2020)
This study examines the Talent Management Practice (TMP) and gender imbalance in Institutions of higher learning (IHL): the impact on Institutional performance. The researchers employed the post-positivist design. A structured questionnaire using the Linkert scale was used to collect empirical data. Partial Least Square equation modeling was used to analyze the data. PLS model was used because the study involved many constructs, and our objective is to provide a better understanding of increasing complex variables by exploring theoretical extensions on TMP, and the latent variables scores were used for follow-up analysis (Hair et al. 2017).The findings of the study revealed a significant positive relationship between TMP (culture and training) and Institutional Performance. The implication is that for IHL to achieve efficiency they must continue to invest in talent training and promotion gender equality through mentorship, child health careand early learning facilities, and research grants programs should be ingrainedinto IP as part of the operational culture.